2007
DOI: 10.1007/bf03026796
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Ropivacaine neurotoxicity at clinical doses in interscalene brachial plexus block

Abstract: Purpose: To describe a case of ropivacaine toxicity following an ultrasound guided interscalene block and discuss the possible mechanisms involved. Clinical features:A 76-yr-old woman with multiple myeloma was scheduled for open reduction and internal fixation following a pathological fracture of her left upper humerus. She developed central nervous system toxicity with ropivacaine 15 min after a carefully placed ultrasound-guided interscalene catheter. The dose of ropivacaine was within recommended limits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 14 publications
0
41
0
3
Order By: Relevance
“…Therefore, local anesthetics are generally used at the lowest effective concentration to reduce neurotoxicity in clinical settings. Ropivacaine hydrochloride exhibits a lower toxicity than bupivacaine hydrochloride 27, 28 , but it also produces nerve damage in nerve block 7, 8 . DRG is the target of local anesthetics in spinal anesthesia, and DRG toxicity damage causes abnormal sensation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, local anesthetics are generally used at the lowest effective concentration to reduce neurotoxicity in clinical settings. Ropivacaine hydrochloride exhibits a lower toxicity than bupivacaine hydrochloride 27, 28 , but it also produces nerve damage in nerve block 7, 8 . DRG is the target of local anesthetics in spinal anesthesia, and DRG toxicity damage causes abnormal sensation.…”
Section: Discussionmentioning
confidence: 99%
“…However, high concentrations or long exposure times of local anesthetics to neurons also results in neuronal damage 5, 6 . Ropivacaine hydrochloride is commonly used in peripheral nerve block or spinal analgesia with a long exposure time, but it also causes nerve damage and abnormal sensations similar to other local anesthetics 7, 8 . A multicenter study reported that the occurrence rate of local anesthetic-induced transient neurological syndrome (TNS) was 8.1% 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Nishiyama and Komatsu, [2] has stated that convulsions seen at the 10th min of interscalene block in a sedated 72 years old female patient might be due to injection into a small vein in the area and negative aspiration test could be the result of a needle touching to the vein wall. Dhir et al, [9] had reported that the convulsions that appear 15 min after the injection of local anesthetic might be due to systemic absorption but found out that the catheter was located intravascularly when investigated with doppler device. In general, intravenous injections cause to late reactions depending on the dose during the interscalene block; still very small dose administered intra-arterially may lead to serious reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to alerting the practitioner to the possibility of an intravascular injection, epinephrine decreases peak plasma concentration (C-max) of local anesthetic; it delays the time to peak plasma concentration (T-max) and decreases the bioavailability of the rapid absorption phase, all of which serve to reduce local anesthetic toxicity. 92 Local anesthetic systemic toxicity 375…”
Section: Prevention Of Local Anesthetic Toxicitymentioning
confidence: 99%